AI APPLICATIONS IN LANGUAGE LEARNING - Norbutayev Xushnud Yeshnazarovich, (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article analyzes the application of artificial intelligence (AI) tools in foreign language education, their effectiveness, and potential in contemporary teaching environments. It examines AI-based interactive platforms, virtual assistants, automated testing systems, and language learning applications, highlighting their advantages for both individual and group learning. The article also explores methodological and psychological aspects of AI-assisted language instruction.